(untitled) (Eurasian Research Bulletin, 2022)
The article identifies and describes lexical units denoting parts of the body in the phraseological funds of the English and Uzbek languages. The totality of these lexical units are presented in the structure of the lexico-semantic field (LSF), the construction of which is based on the semantics of the lexical unit, the possibility of its figurative use and taking into account fixed associations.